2018
DOI: 10.24990/injec.v2i2.144
|View full text |Cite
|
Sign up to set email alerts
|

Application of “Six Rights” on Medication Administration by Nurse and Patient Satisfaction

Abstract: Introduction:Giving the medications, nurse should pay attention to the principles of "six of rights", namely: right of patient, right medication, right dose, right way, right time, and right documentation. There are more than a half of nurses in a ward who are not provide medications in accordance with the Standard Operational Procedure (SOP). The purpose of this study was to determine of the relationship between applications of Standard Operational Procedure (SOP) six rights of medication administration by nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…9 Participants reported that following the six rights (right patient, right drug, right time, right dose, right route of administration and documentation) and double-checking of medications might be important to prevent errors as in some studies it is considered the best strategy to avoid errors and increase patient safety. 22 While regarding double-checking, Armitage argued that it might increase the occurrence of errors because nurses may lose their concentration relying on other colleagues, therefore, Jarman et al recommend following single checking procedures which helps the nurses to concentrate and increases their level of responsibility while administering medications. 23,24 Furthermore, nurses perceived the existence of a computerised system for drug administration to reduce the occurrence of errors, which was in agreement with the findings from previous studies.…”
Section: Never N (%)mentioning
confidence: 99%
“…9 Participants reported that following the six rights (right patient, right drug, right time, right dose, right route of administration and documentation) and double-checking of medications might be important to prevent errors as in some studies it is considered the best strategy to avoid errors and increase patient safety. 22 While regarding double-checking, Armitage argued that it might increase the occurrence of errors because nurses may lose their concentration relying on other colleagues, therefore, Jarman et al recommend following single checking procedures which helps the nurses to concentrate and increases their level of responsibility while administering medications. 23,24 Furthermore, nurses perceived the existence of a computerised system for drug administration to reduce the occurrence of errors, which was in agreement with the findings from previous studies.…”
Section: Never N (%)mentioning
confidence: 99%
“…The critical issue that nurses must pay attention to when giving a drug is the six rights principle which includes right patient, right medication, right time, right dose, right route and right documentation (Hughes & Blegen, 2008;Department of Health Government of Western Australia, 2013). Giving drugs by applying the six rights principle also gives satisfaction to the patient; this is evident in research conducted by Kartika & Melani (2018) that shows that 50% of patients are satisfied with the application of the six rights principle when administering the drug. Nurses are the health workers who most often find and detect medication errors in the prescription order phase before being given to patients.…”
Section: Roles and Responsibilities Of Nurses In Medication Safetymentioning
confidence: 97%
“…They are always trying to minimize the occurrence of MAEs by implementing the six aspects of rightness pertaining to the safe administration of medication. 11 Nevertheless, the possibility of committing errors always exists. Unfortunately, when medication errors occur, nurses may avoid admitting the occurrence of errors because of the fear of consequences.…”
Section: Introductionmentioning
confidence: 99%